Human Dental Pulp Stem Cells Modulate Cytokine Production in vitro by Peripheral Blood Mononuclear Cells From Coronavirus Disease 2019 Patients - Croci, Stefania; Bonacini, Martina; Dolci, Giovanni; Massari, Marco; Facciolongo, Nicola; Pignatti, Elisa; Pisciotta, Alessandra; Carnevale, Gianluca; Negro, Aurelio; Cassone, Giulia; Muratore, Francesco; Belloni, Lucia; et al. (Frontiers in Cell and Developmental Biology, 2021)
A subset of patients infected with Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) develop a condition of hyper-inflammation which can cause multi-organ damage and the more severe forms of coronavirus disease 2019 (COVID-19). Mesenchymal stem cells (MSCs) can promote tissue regeneration and modulate immune responses, thus have the rationale requirements to be used to counteract SARS-CoV-2 induced pneumonia and hyper-inflammation. The aim of the present study was to gain insight into possible mechanisms of action of MSCs obtained from human dental pulp (DPSCs) in COVID-19 patients. We investigated the concentrations of 18 cytokines in supernatants of peripheral blood mononuclear cells (PBMCs) obtained from COVID-19 patients cultured in vitro alone and in contact with DPSCs. The modulation of cytokines in PBMCs was confirmed by real-time PCR. IL-6 was the sole cytokine detected in supernatants of DPSCs. In resting conditions, co-culture increased IL-1b, IL-2, IL-5, IL-6, IL-10, IL-18, TNFa and GM-CSF levels. When PBMCs were activated with anti-CD3/CD28 antibody coated beads, co-culture increased IL-6 and GM-CSF whereas decreased IFNg, TNFa, IL-2, IL-5, IL-9, IL-10, IL-12(p70), IL-17A, IL-18, IL-21, IL-23, IL-27 levels. Concentrations of IL-1b, IL-4, IL-13 and IL-22 were not affected. The comparison of cytokine concentrations in supernatants of PBMCs from COVID-19 patients versus healthy subjects revealed lower concentrations of IL-10 and higher concentrations of IL-18 in supernatants of CD3/CD28 activated PBMCs from COVID-19 patients. Results are explorative but indicate that DPSCs can modulate the production of cytokines deregulated in COVID-19 patients, supporting their potential use in COVID-19.